Noninvasive Wireless Sensor PFMT Device for Pelvic Floor Muscle Training - Jui-Fa Chen; Huann-Cheng Horng; Wei-Chuan Lin; Kun-Hsiao Tsai (International Journal of Distributed Sensor Networks)
Urinary incontinence is a common problem among adults. Studies have shown up to 70% improvement in stress incontinence symptoms following appropriately performed pelvic floor exercise. This improvement is evident across all age groups. In this study, we cooperated with a doctor of the Department of Obstetrics and Gynecology, Taipei Veterans General Hospital, Taiwan. We developed a noninvasive device with the purpose of helping patients commence and perform pelvic floor muscle training (PFMT). This device consists of a PFMT device, an Arduino control board, a force sensor, a Bluetooth device, and an SD card. The objectives of this study are to train patients to inhibit detrusor contraction voluntarily and to contract periurethral muscles selectively. The system records and analyzes sensor data and provides voice prompts during PFMT exercise for patients at hospitals or their homes. Meanwhile, it tracks patients' PFMT exercise at home, and doctors can contact patients for additional visitation(s) if necessary.